How arbitrary are the weights assigned to books in performance-based research funding? An empirical assessment of the weight and size of monographs in Flanders. Issue 6 (19th November 2018) - Verleysen, Frederik T.; Engels, Tim C.E.
Abstract : Purpose: The purpose of this paper is to present an empirical assessment of the weight assigned to monographs in the publication indicator of the performance-based research funding system (PRFS) in Flanders, Belgium. By relating publication weight to publication size the authors offer an alternative perspective on the production of scholars who publish monographs. This perspective on weights is linked to the aggregation level at which PRFS indicators are used: the national/regional one as opposed to the local one. In Flanders as elsewhere the publication indicator designed for funding distribution between universities has sometimes trickled down to institutions, their faculties and departments. Design/methodology/approach: As an alternative indicator of scholarly production the authors propose the median number of pages of a publication type. Measuring the size of publications allows to compare the weight ratio between monographs and journal articles in the publication indicator to their size ratio in the VABB-SHW database. The authors compare two levels, one of four universities and one of 16 disciplines. Findings: Median publication size differences between disciplines are much larger than those between universities. This indicates that an increase of monographs' weight in the publication indicator would hardly affect funding distribution at the regional level. Disciplines with a relatively large share of monographs, however, would contribute more to the publication indicator. Hence an increase of monographs' weight might provide a better balance between fields and between publication types. Originality/value: This paper presents a thought experiment regarding the weight assigned to different publication types in the publication indicator of the Flemish PRFS: what would happen if this weight were replaced by the median number of pages of a publication type? In doing so, we highlight that such weighting schemes play an important role in finding a balance between fields of research. The sizeable differences between weight and size ratios offer a new and critical perspective on the weighting schemes currently used in PRFS, also in other countries.